2006
DOI: 10.1029/2005jb003754
|View full text |Cite
|
Sign up to set email alerts
|

On the relative importance of self‐gravitation and elasticity in modeling volcanic ground deformation and gravity changes

Abstract: [1] Elastic half-space models, widely used to interpret displacements and gravity data in active volcanic areas, usually compute the displacement response to dilatational sources that simulate a change in pressure of the magma chamber. Elastic-gravitational models allow the computation of gravity, deformation, and gravitational potential changes due to pressurized magma cavities and intruding masses together. This type of model takes into account the mass interaction with the self-gravitation of the Earth thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 46 publications
0
21
0
Order By: Relevance
“…BATTAGLIA and SEGALL (2004) and CHARCO et al (2006) performed a dimensional analysis and scaling of the elastic-gravitational problem in order to gain insight into the approximations and solutions without actually attempting a formal solution. From dimensionalized parameters and using typical parameter values for volcanic areas, they found that terms depending on G and g in the equations (1) and (2) are negligible in the computation of the displacement field.…”
Section: Mass Coupling and Topographic Interactionmentioning
confidence: 99%
“…BATTAGLIA and SEGALL (2004) and CHARCO et al (2006) performed a dimensional analysis and scaling of the elastic-gravitational problem in order to gain insight into the approximations and solutions without actually attempting a formal solution. From dimensionalized parameters and using typical parameter values for volcanic areas, they found that terms depending on G and g in the equations (1) and (2) are negligible in the computation of the displacement field.…”
Section: Mass Coupling and Topographic Interactionmentioning
confidence: 99%
“…When computing volcanic loading effects, coupling between gravity and elasticity is negligible for displacements in the spatial scale associated with volcano monitoring, but the absolute effects of the existing gravity field become important when rigidity decreases ͑i.e., viscoelastic media͒ ͑Fernández et al, 1997; Battaglia and Segall, 2004;Charco et al, 2006͒. Coupling is a second-order effect that cannot be ignored in flat half-space models when a mass source term…”
Section: The Effect Of Topographymentioning
confidence: 99%
“…Moreover, for spherical sources the topography effect is due primarily to the distance of the free surface from the magma source rather than the local shape of the free surface (Williams and Wadge, 1998). As a result, no differences are found between numerical and analytical solutions, if the topography effect is approximated by replacing in the analytical expressions the flat reference surface with the real elevation of the observation point Charco et al, 2009). At the observation point (x, y, z) the analytical solution of the thermomagnetic change T due to a source centered at (x 0 , y 0 , z 0 ) is expressed as follows (Blakely, 1995):…”
Section: Forward Problem: Fem Solutionmentioning
confidence: 89%
“…The last two contributions have a significant effect on the magnitude of the predicted gravity changes when the source resides at shallow depths (Bonafede and Mazzanti, 1998;Charco et al, 2006;Currenti et al, 2007). In case of deep pressure sources these contributions are below microgravity accuracy (Battaglia and Segall, 2004;Currenti et al, 2007) and are negligible compared to those produced by the input of new mass.…”
Section: Forward Problem: Fem Solutionmentioning
confidence: 97%
See 1 more Smart Citation